A MIF-like effector suppresses plant immunity and facilitates nematode parasitism by interacting with plant annexins. (31st July 2019) - Zhao, Jianlong; Li, Lijuan; Liu, Qian; Liu, Pei; Li, Shuang; Yang, Dan; Chen, Yongpan; Pagnotta, Sophie; Favery, Bruno; Abad, Pierre; Jian, Heng
Abstract : The plant-parasitic nematode Meloidogyne incognita secretes MIF-like proteins into plant tissues, and MiMIF-2 interacts with two plant annexins to suppress plant immune responses and promote parasitism. Abstract: Plant-parasitic nematodes secrete numerous effectors to facilitate parasitism, but detailed functions of nematode effectors and their plant targets remain largely unknown. Here, we characterized four macrophage migration inhibitory factors (MIFs) in Meloidogyne incognita resembling the MIFs secreted by human and animal parasites. Transcriptional data showed MiMIFs are up-regulated in parasitism. Immunolocalization provided evidence that MiMIF proteins are secreted from the nematode hypodermis to the parasite surface, detected in plant tissues and giant cells. In planta MiMIFs RNA interference in Arabidopsis decreased infection and nematode reproduction. Transient expression of MiMIF-2 could suppress Bax- and RBP1/Gpa2-induced cell death. MiMIF-2 ectopic expression led to higher levels of Arabidopsis susceptibility, suppressed immune responses triggered by flg22, and impaired [Ca 2+ ]cyt influx induced by H2 O2 . The immunoprecipitation of MiMIF-2-interacting proteins, followed by co-immunoprecipitation and bimolecular fluorescence complementation validations, revealed specific interactions between MiMIF-2 and two Arabidopsis annexins, AnnAt1 and AnnAt4, involved in the transport of calcium ions, stress responses, and signal transduction. Suppression of expression or overexpression of these annexins modified nematode infection. Our results provide functional evidence that nematode effectors secreted from hypodermis to the parasite cuticle surface target host proteins and M. incognita uses MiMIFs to promote parasitism by interfering with the annexin-mediated plant immune responses.